Analisis Status Gizi dan Kebutuhan Kalori Peserta Didik Usia 7-10 Tahun - Prayogo Dino Saputro; Hendra Mashuri; Ni Putu Dwi Sucita Dartini (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the nutritional status and dietary needs of students aged 7–10 years at SDN 3 Sesetan. Using a quantitative descriptive survey method, the research involved total sampling of all 86 second-grade students (40 boys and 46 girls). Data were collected using a stadiometer and weighing scale. Descriptive percentage analysis was used to interpret the data. The results showed that among the participants, 3 students (4%) were classified as severely obese, 2 students (2%) as mildly obese, 32 students (37%) had ideal nutritional status, and 49 students (57%) were underweight. The average daily calorie requirement was 1,935.50 kcal. Macronutrient analysis indicated an average daily requirement of 1,195.01 kcal from carbohydrates, 298.75 kcal from protein, and 497.92 kcal from fat. These findings reveal that a significant number of students have not yet reached optimal nutritional status. The variability in nutritional needs suggests the importance of attention and collaboration from both physical education (PJOK) teachers and parents to support students' health and development.